MODEL MEDIASI KEPUTUSAN PEMBELIAN GEN Z PADA PELANGGAN KAFE SENANDIKA FIRDAUS: KEPUTUSAN PEMBELIAN GEN Z - Leny Kalyana; Nurul Hafizah; Didik Gunawan; Indra Welly Arifin (ITB AAS Indonesia Surakarta, 2025)
This study uses perceived quality as a mediating variable to determine how lifestyle and reference price influence purchasing decisions of Generation Z consumers at Kafe Senandika Firdaus. 96 Generation Z consumers who have visited Kafe Senandika in the past six months were given a questionnaire as part of the quantitative research methodology. The analytical approach of this study consists of assessing the instrument, namely the validity and reliability tests, and then utilizing SmartPLS version 3.0 to analyze the structural model (inner model) using partial least squares (PLS-SEM). The quality of the model fit, the coefficient of determination (R²), and the indirect effect (mediation) as well as the t-statistic test for hypothesis testing are all included in the structural model. The results of data processing using SmartPLS 3.0 from this study indicate that Lifestyle has a direct positive and significant effect on Purchasing Decisions, Reference Price has a direct positive and significant effect on Purchasing Decisions, perceived quality has a direct positive and significant effect on Purchasing Decisions, Lifestyle has a significant effect on Perceived Quality and Reference Price has a significant effect on Perceived Quality. Furthermore, the results of this study show that lifestyle influences purchasing decisions indirectly through perceived quality and reference prices influence purchasing decisions indirectly through perceived quality.